Formulate Arabic Learning Objectives in Early Childhood Education Unit - Asmawi, Muhammad Nur; Kasmiati, Kasmiati (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
As a characteristic of Islam, the Arabic language curriculum has been taught in Islamic-based early childhood education units. This research is important because Arabic has become an international language used as a tool of international communication. Hence, skills and abilities in speaking Arabic properly are competencies that students at all levels of education must possess. This research aims to find, identify, and explain the objectives of learning Arabic in Islamic-based early childhood education units. The research was conducted using a qualitative-descriptive-and textual model, namely research using a database of textual documents that were studied and presented descriptively from a scientific point of view of learning objectives, early childhood, and early childhood education units. The research results in areFirst, The instrumental objective of Arabic is taught so that early childhood can use Arabic to understand, get used to, and practice the teachings, worship, and prayers found in the Al-Qur'an and Al-Hadith. Second, for Integrative-communicative purposes, Arabic is taught so that children can have communication skills in Arabic. Third, pedagogical goals include Arabic in learning activities to master Arabic knowledge, skills, and values ​​in early childhood.